Solving the Faddeev-Merkuriev Equations in Total Orbital Momentum Representation via Spline Collocation and Tensor Product Preconditioning (Communications in Computational Physics, 2021)
The computational approach for solving the Faddeev-Merkuriev equationsin total orbital momentum representation is presented. These equations describe a system of three quantum charged particles and are widely used in bound state and scattering calculations. The approach is based on the spline collocation method and exploitsintensively the tensor product form of discretized operators and preconditioner, whichleads to a drastic economy in both computer resources and time.
Keywords: Faddeev-Merkuriev equations; total orbital momentum representation; spline collocation; tensor product preconditioner.